ANALISIS SISTEM PENGGAJIAN TENAGA KONTRAK UIN SUNAN KALIJAGA YOGYAKARTA - Muhammad Subkhan; Wahyu Setianingsih; Ruddy Tri Santoso (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
UIN (Universitas Islam Negeri) Sunan Kalijaga is an Islamic State University that previously named IAIN SunanKalijaga. It was established in 26 September 1951 and it was one of the oldest university that established by the Ministry of Religious Affairs. As for the human resources whose working in the university, there are public servants who appointed to work there by the National Administrative system and also contract workers. The contract workers are the employee of UIN SunanKalijaga that legally being appointed by the Rector of the University through a decree signed by the Rector itself. The contract system will be renewed annually, started in the beginning of the year. Within the contract, there are terms such as rights and obligations including the amount of the salary. And, the amount of the salary will be changed every 3 years. There basic calculations for the salary system by referring the current national’s public servant salary system and minimum local wage system. Therefore, based on the issue above, this thesis would like to highlight some questions in order to answer some questions; what factors affecting the change of the salary system for the contract workers in UIN SunanKalijaga, Why to factors becoming push factors in the changing of salary system of contract workers and how the current reality of contract workers salary system at UIN Sunan Kalijaga. The aim of the research will be to identify what factors causing the changing of salary system at UIN SunanKalijaga, and to analyse the push factors as well to evaluate the salary system of contract workers at UIN SunanKalijaga. Meanwhile the theoretical framework being employed on this research will be the Salary Theory and Compensation theory. And, as for the method of research, there will be descriptive qualitative and the data will be gathered through primary and secondary data. Documents will be used as source of information and respondents will interviewed to gain some insights of the policy.